Follicular thyroid lesions: Is there a discriminatory potential in the computerized nuclear analysis? - Valentim, Flávia O. [UNESP]; Coelho, Bárbara P. [UNESP]; Miot, Hélio A. [UNESP]; Hayashi, Caroline Y. [UNESP]; Jaune, Danilo T. A. [UNESP]; Oliveira, Cristiano C. [UNESP]; Marques, Mariângela E. A. [UNESP]; Tagliarini, José Vicente [UNESP]; Castilho, Emanuel C. [UNESP]; Soares, Paula; Mazeto, Gláucia M. F. S. [UNESP] (Bioscientifica, 2018)
Background: Computerized image analysis seems to represent a promising diagnostic possibility for thyroid tumors. Our aim was to evaluate the discriminatory diagnostic efficiency of computerized image analysis of cell nuclei from histological materials of follicular tumors. Methods: We studied paraffin-embedded materials from 42 follicular adenomas (FA), 47 follicular variants of papillary carcinomas (FVPC) and 20 follicular carcinomas (FC) by the software ImageJ. Based on the nuclear morphometry and chromatin texture, the samples were classified as FA, FC or FVPC using the Classification and Regression Trees method. Results: We observed high diagnostic sensitivity and specificity rates (FVPC: 89.4% and 100%; FC: 95.0% and 92.1%; FA: 90.5 and 95.5%, respectively). When the tumors were compared by pairs (FC vs FA, FVPC vs FA), 100% of the cases were classified correctly. Conclusion: The computerized image analysis of nuclear features showed to be a useful diagnostic support tool for the histological differentiation between follicular adenomas, follicular variants of papillary carcinomas and follicular carcinomas.
Keywords: Adenocarcinoma; Carcinoma; Cell nucleus; Follicular; Histology; Papillary; Thyroid neoplasms